Intracranial Hypertension in Siblings with Infantile Hypercalcemia - Dufek, Stephanie; Seidl, Rainer; Schmook, Maria; Arbeiter, Klaus; Müller-Sacherer, Thomas; Heindl-Rusai, Krisztina (Neuropediatrics, 2015)
Background Idiopathic intracranial hypertension is a clinical condition with elevated intracranial pressure of uncertain etiology. Although various underlying causes are suspected and familial occurrence has also been reported, however, it still remains an unexplained phenomenon.Case Report We report the case of dizygotic siblings with a known CYP24A1 mutation resulting in chronic hypercalcemia and impairment of kidney function. At the same point in time both of them developed intracranial hypertension resistant to conservative therapy necessitating therefore ventriculoperitoneal shunt implantation. In both children magnetic resonance imaging showed slightly hypoplastic sinus transversus as the potential underlying cause.Conclusion The simultaneous clinical presentation could be due to a genetic factor or might be a component of the underlying disease or the consequence of its treatment. Further cases and clinical experience are needed to clarify this issue.
Keywords: idiopathic intracranial hypertension; idiopathic infantile hypercalcemia; pseudotumor cerebri; CYP24A1 mutation